Chemical constituents from the stem barks of Polyscias serrata Balf - Anh, Le Thi Tu; Ha, Nguyen Thi Thu; Tra, Nguyen Thanh; Ninh, Bui Hai; Tiep, Nguyen Khac; Son, Ninh The (Vietnam Journal of Science and Technology, 2022)
Plants of the genus Polyscias (the family Araliaceae) are represented as perennial shrubs and are commonly cultivated in southeastern Asia and the Pacific regions. Pharmacological studies revealed that Polyscias crude extracts and their isolated compounds exhibited a variety of biological activity, such as antibacterial, antifungal, cytotoxic, immuno-stimulant, wound healing and anti-asthmatic activities. For the first time, phytochemical study on the methanol (MeOH) extract of the stem barks of Vietnamese species Polyscias serrata Balf. (locally named Dinh lang rang) resulted in the isolation and NMR (Nuclear Magnetic Resonance)-determination of six compounds 1-6. They include one nucleobase uracil (1), two nucleosides uridine (2) and adenosine (3), one alkaloid indole-3-carboxylic acid (4), one mono-phenol glucoside koaburside (5), and one saponin randianin (6). The chemical structures of these phytochemicals were elucidated by physicochemical, the 1D-NMR [1H, 13C-NMR, and DEPT (Distortionless Enhancement by Polarization Transfer)], the 2D-NMR [HSQC (heteronuclear single quantum coherence), HMBC (Heteronuclear Multiple Bond Correlation), and COSY (correlation spectroscopy)] spectral, and ESI-MS (Electron Spray Ionization-Mass Spectrum) data. This is the first time that compounds 2-6 have been obtained from the genus Polyscias. In agreement with various reports, the nitrogenous compounds and triterpene saponins can be seen as characteristic metabolites of genus Polyscia